Design integration of novel porous ceramic evaporative cooling systems - Vallejo, Juan (2018)
The rise in demand of air conditioning is unsustainable. Concerns over the subsequent greenhouse emissions and global climate change led to a recent rise of interest by professionals in the building sector in the application of ancient cooling techniques in contemporary architecture to reduce energy demand and deliver healthy and comfortable environments. Despite the successful progress, further research is still needed to make passive cooling systems appealing to a wider audience and to address the limitations found in previous work.